2019
DOI: 10.1101/19009175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eligibility for Subcutaneous Implantable Cardioverter Defibrillator in Congenital Heart Disease

Abstract: Background: The goals of this study were: assess left-and right-sided subcutaneous implantable cardioverter-defibrillator (SICD) eligibility in adult congenital heart disease (ACHD) patients, use machine learning to predict SICD eligibility in ACHD patients, and transform 12-lead ECG to S-ICD 3-lead ECG, and vice versa. Methods: ACHD outpatients (n=101; age 42±14 y; 52% female; 85% white; left ventricular ejection fraction (LVEF) 56±9%) were enrolled in a prospective study. Supine and standing 12-lead ECG was … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…Mathematically, it is not possible to achieve the reported 83% rate of eligibility per written findings, but, instead, figure 1 provides results more consistent with previous studies. [2][3][4] The authors 1 did not discuss possible reasons for disagreement of their findings with previous studies. It is essential to discuss the limitations of the study in order for the reader to gain perspective of the study.The methods included the use of an automated Boston-Scientific screening test.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…Mathematically, it is not possible to achieve the reported 83% rate of eligibility per written findings, but, instead, figure 1 provides results more consistent with previous studies. [2][3][4] The authors 1 did not discuss possible reasons for disagreement of their findings with previous studies. It is essential to discuss the limitations of the study in order for the reader to gain perspective of the study.The methods included the use of an automated Boston-Scientific screening test.…”
mentioning
confidence: 85%
“…The limitations in the study design and conduct could at least partially explain the difference in the reported results with other studies. [2][3][4] Also, the study 1 raised questions about the appropriateness of utilized statistical analyses. For appropriate paired comparison of S-ICD ineligibility in different positions (standing and supine) on the left and right sides, McNemar's χ 2 statistic has to be used.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For the development and validation of the algorithm, we used the data of clinical studies conducted at the Oregon Health & Science University (OHSU), with available both (1) digitally recorded ECGs and (2) printed on paper ECGs. [11][12][13][14] All studies were approved by the OHSU Institutional Review Board, and all participants signed informed consent before entering the study.…”
Section: 1study Population and Ecg Recordingmentioning
confidence: 99%